2022
DOI: 10.3390/biology11060901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet Consistency on Rat Mandibular Growth: A Geometric Morphometric and Linear Cephalometric Study

Abstract: Background: Our study intended to investigate the null hypothesis that there is no effect of diet consistency on rat mandibular growth. Methods: A total sample of 24 female wistar rats, 30 days old, was used in this study. In the first group, the rats were fed soft diet and in the second group, they were fed hard diet for 60 days. On the 60th day, the rats were sedated and lateral cephalometric X-rays were taken. Lateral cephalometric X-rays were digitized with 7 craniofacial landmarks for the linear measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The average posterior height of the mandible (as represented by L7) was shorter in all rats who received a liquid nutrition diet. Our data correspond to the results of a previous study showing that the posterior height of the mandible appears to be shorter when the diet is more likely soft [25, 26].…”
Section: Discussionsupporting
confidence: 91%
“…The average posterior height of the mandible (as represented by L7) was shorter in all rats who received a liquid nutrition diet. Our data correspond to the results of a previous study showing that the posterior height of the mandible appears to be shorter when the diet is more likely soft [25, 26].…”
Section: Discussionsupporting
confidence: 91%
“…There was a decrease in length and posterior height in the soft diet group. The morphometric superimposition revealed differences in the condyle, the angle of the mandible, and the body of the mandible [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grunheid et al in 2011 had a similar hypothesis but a different experimental animal (New Zealand white rabbits), and their results indicated that a moderate reduction in masticatory functional load does not drastically affect the remodeling rate [ 38 ]. In 2022, Tsolakis et al, by using Wistar rats as the experimental animal, found that a soft diet resulted in a smaller condyle and decreased angle of the mandible as well as the body of the mandible [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common orthodontic problems is Class II malocclusion which is defined as the distal position of the mandibular first molar relative to the maxillary first molar according to Angle [ 1 , 2 ]. It presents a mean global distribution of 19.56% in permanent dentition [ 3 ] and a 12 to 32% range in Caucasians [ 4 , 5 , 6 , 7 ], while mandibular retrognathia, one of its major causes, seems to be influenced by the diet and function of the surrounding soft tissue [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%